P171 Augmented endoscopy for surveillance of colonic inflammatory bowel disease: systematic review with network meta-analysis. (25th January 2019) - Castiglione, F; Imperatore, N; Testa, A; De Palma, G D; Pellegrini, L; Caporaso, N; Rispo, A; ,
Abstract: Background: Considering the high risk of dysplasia and cancer in inflammatory bowel disease (IBD), surveillance is advocated. However, international guidelines do not reach a uniform recommendation on the way to perform surveillance. We performed a systematic review with a meta-analysis to assess the best endoscopic surveillance strategy in colonic IBD. Methods: The systematic review was performed in PubMed/MEDLINE, EMBASE, SCOPUS and Cochrane databases to identify studies comparing white light endoscopy (WLE) and augmented endoscopy (AE) in the detection of dysplasia or neoplasia in colonic IBD. Sub-analyses between dye-spray chromoendoscopy (DCE), narrow-band imaging (NBI), I-SCAN, full-spectrum endoscopy (FUSE) and auto-fluorescence imaging (AFI), and the role of random vs. targeted biopsies were also performed. Furthermore, a meta-regression and a network meta-analysis were also performed. Results: Twenty-seven studies (6167 IBD patients with 2024 dysplastic lesions) met the inclusion criteria. There was no publication bias. AE showed a higher likelihood of detecting dysplastic lesions than WLE (19.3% vs. 8.5%, OR = 2.036), with an incremental yield (IY) of 10.8%. DCE (OR = 2.605) and AFI (OR = 3.055) had higher likelihood of detecting adenomas than WLE; otherwise, I-SCAN (OR = 1.096), NBI (OR = 0.650) and FUSE (OR = 1.118) were not superior to WLE. Dysplasia was found in 1256/7267 targeted biopsies (17.3%) and in 363/110040 random biopsies (0.33%) (OR = 66.559, IY = 16.9%). Meta-regression found no variable impacting the efficacy of AE techniques. Network meta-analysis identified a significant superiority of DCE on WLE in detecting dysplasia (OR = 2.12), while no other single technique was found to be superior to all others in adenoma detection. Conclusions: AE, especially DCE, was associated with higher likelihood of discovering dysplastic lesions than WLE. Chromoendoscopy with targeted biopsies is the best endoscopic technique for IBD surveillance.